2021
DOI: 10.1186/s12879-021-06716-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance of SARS-CoV-2 antigen testing in symptomatic and asymptomatic adults: a single-center evaluation

Abstract: Background Antigen testing offers rapid and inexpensive testing for SARS-CoV-2 but concerns regarding performance, especially sensitivity, remain. Limited data exists for use of antigen testing in asymptomatic patients; thus, performance and reliability of antigen testing remains unclear. Methods 148 symptomatic and 144 asymptomatic adults were included. A nasal swab was collected for testing by Quidel Sofia SARS IFA (Sofia) as point of care. A nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 11 publications
2
18
1
1
Order By: Relevance
“…[36] In alignment with prior studies, we found the sensitivity of rapid antigen testing to be significantly higher later in the course of infection (rapid antigen tests collected on the same day or after RT-PCR) and among residents exhibiting COVID-19 symptoms. [37,38] However, contrary to previous findings, we found the specificity to be significantly lower among symptomatic residents than among asymptomatic residents. [38][39][40] While, the magnitude of this difference was minimal for the one-rapid antigen test strategy (specificity among symptomatic residents was 5% lower than asymptomatic residents), the difference was larger (13%) for the three-rapid antigen test strategy.…”
Section: Discussioncontrasting
confidence: 99%
“…[36] In alignment with prior studies, we found the sensitivity of rapid antigen testing to be significantly higher later in the course of infection (rapid antigen tests collected on the same day or after RT-PCR) and among residents exhibiting COVID-19 symptoms. [37,38] However, contrary to previous findings, we found the specificity to be significantly lower among symptomatic residents than among asymptomatic residents. [38][39][40] While, the magnitude of this difference was minimal for the one-rapid antigen test strategy (specificity among symptomatic residents was 5% lower than asymptomatic residents), the difference was larger (13%) for the three-rapid antigen test strategy.…”
Section: Discussioncontrasting
confidence: 99%
“…It’s critical to confirm an antigen test result with a PCR test, especially if the result of the antigen rapid test contradicts the clinical setting. Therefore, PCR tests remain the gold standard, and their value remains high [ 73 , 75 ]. To be noted antigen rapid tests are typically used on symptomatic individuals since they perform best in symptomatic individuals and within a particular number of days of symptom onset [ 74 ].…”
Section: Results and Overall Findingsmentioning
confidence: 99%
“…Frequent screening for SARS-CoV-2 in asymptomatic populations using antigen-based POCT has a very low detection rate and a high false-alarm rate. 24 Therefore, before using LFIA for COVID-19 screening, the characteristic distribution of the infected population, the accuracy of the LFIA kit, and the variation in sensitivity over time need to be carefully evaluated. When using LFIA for COVID-19 screening, it is necessary to increase the number of LFIA tests or combine LFIA with NAAT tests, especially in asymptomatic people and persons with symptomatic episodes >5 days.…”
Section: Radmentioning
confidence: 99%